COLLABORATIVE GOVERNANCE IN INTEGRATED MSME MANAGEMENT - Reswari, Tiara Retno Wulan (Srawung: Journal of Social Sciences and Humanities, 2023)
Micro, Small and Medium Enterprises (MSMEs), have a strategic role in Indonesia economy. This role is shown through data from Ministry of Cooperatives and SMEs in 2019 which shows that MSMEs are able to absorb a workforce of 96.92% of the total number of MSMEs that reach 64 million with the contribution to National GDP reached 60.51%. Unfortunately, MSMEs still have several problems with different percentages including capital, 51.09%, marketing, 34.72%, raw materials, 8.59%, employment, 1.09%, transportation distribution, 0.22%, and others 3.93%. Referring to some of the problems mentioned above, the government established the 2022 Integrated Management of MSMEs as stated in the 2022 Government Work Plan. This research aims to explore the synergy of collaborative governance in increasing the contribution of MSMEs to national economic recovery. This effort is a form of collaborative governance that involves various stakeholders, namely the Regional Government, related Ministries/Institutions, BUMN, BUMD, and private off takers with the Ministry of Cooperatives and SMEs as the leading sector. This management is a form of integrated management in one central area which aims to increase added value and product competitiveness. The results of this research indicate that of the four variables in collaborative governance it is necessary to strengthen the institutional design variables.